(untitled) (Proceedings of Southern Federal University. Philology, 2020)
It is analyzed the episode of a child leaving home for school in the novels «David Copperfield» and «Bleak House» by Charles Dickens and «Jane Eyre» by Charlotte Bronte. Studying at a boarding school and leaving home for it was quite a typical episode of life for the Victorians, but for the main characters of C. Dickens’ and Ch. Bronte’s novels the circumstances of leaving home are paradoxical and unusual so much, that it becomes a part of the initiation process. All of them are not happy at home. In fact, being orphans brought up by distant relatives (aunts or, in David’s case, cruel stepfather who is diminishing the role of David’s mother at home) they, strictly speaking, do not have home at all. That is why the characters are afraid to go to the new place but, at the same time, they are really longing for a change in their lives. Without being homesick, the children go through all other stages of initiation process. During their journeys they shut themselves off other people, feeling lonely among strangers and unsettled by the road. At school, they make new friend (stage of partnership). New people help David, Jane and Esther to know themselves better and reconsider their former experiences. As for the third stage (lethal stage, the experience of death), it is interesting that only Charlotte Bronte gives us the full, traditional representation of it, Dickens prefers his character to experience loss earlier (Esther) or in connection with long left home (David). The fourth stage (the transformation) is the child’s making peace with the world far from home. In all three novels the process of initiation, started with leaving home is necessary for the child to build a strong character, find one’s place in life and achieve happiness. Key words: Victorian novel, Charles Dickens, Charlotte Bronte, child, leaving home for school. DOI 10.18522/1995-0640-2020-4-146-157